Apoptosis in Primary Oral Squamous Cell Carcinomas without Lymph Node Metastases - 严志 汪国民 谢志勇 张汉东 (Current medical science, 2005)
The apoptosis in primary oral squamous cell carcinomas (OSCCs) without lymph node(LN) metastases and its relation with clinical stages and pathological grades was investigated. The terminal deoxynucleotidyl trasferase (TdT)-mediated dUTP nick end labeling (TUNEL) was used to detect the apoptotic cells in 15 cases of OSCCs. The percentage of apoptotic cells among tumor cells were calculated as apoptotic index (AI). The results showed that in all 15 cases of OSCCs,apoptotic cells could be visualized by TUNEL with AI ranging from 0.03 to 0.92 (average 0.32).AI was significantly negatively correlated with pathological grades (P<0. 05). It was concluded that the apoptotic rate was related to the malignant degree of OSCCs without LN metastases.